Tobacco and Oral Health Misinformation on Twitter (X): Implications for Dental Professionals - Eileen L. Han; Benjamin W. Chaffee; Pamela M. Ling (Journal of the California Dental Association)
C.E. Credit Available: A CDA C.E. quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20The practice worksheet is available online: https://doi.org/10.1080/19424396.2025.2486883